Interview with Martin Durazo, artist, New York, 3 October 2012 - Messham-Muir, Kit (StudioCrasher, 2015)
Martin Durazo is a Los Angeles-based artist, whose work deals with issues around narcotic drug-related violence in southern California and the border with Mexico. Durazo’s work draws on abstraction and mass cultural references. The sound quality in this video is less than perfect due to equipment problems; however, I felt it was a great interview with Durazo and worth making available despite its technical issues with sound quality.